Lung Function in Women With and Without Human Immunodeficiency Virus. (23rd May 2022) - Wang, Richard J; Nouraie, Mehdi; Kunisaki, Ken M; Huang, Laurence; Tien, Phyllis C; Anastos, Kathryn; Bhandari, Neha; Bhatt, Surya P; Bolivar, Hector; Cribbs, Sushma K; Foronjy, Robert; Gange, Stephen J; et al.
Abstract: Background: Prior studies have found that human immunodeficiency virus (HIV) infection is associated with impaired lung function and increased risk of chronic lung disease, but few have included large numbers of women. In this study, we investigate whether HIV infection is associated with differences in lung function in women. Methods: This was a cross-sectional analysis of participants in the Women's Interagency HIV Study, a racially and ethnically diverse multicenter cohort of women with and without HIV. In 2018–2019, participants at 9 clinical sites were invited to perform spirometry. Single-breath diffusing capacity for carbon monoxide (DLCO ) was also measured at selected sites. The primary outcomes were the post-bronchodilator forced expiratory volume in 1 second (FEV1 ) and DLCO . Multivariable regression modeling was used to analyze the association of HIV infection and lung function outcomes after adjustment for confounding exposures. Results: FEV1 measurements from 1489 women (1062 with HIV, 427 without HIV) and DLCO measurements from 671 women (463 with HIV, 208 without HIV) met standards for quality and reproducibility. There was no significant difference in FEV1 between women with and without HIV. Women with HIV had lower DLCO measurements (adjusted difference, –0.73 mL/min/mm Hg; 95% confidence interval, −1.33 to −.14). Among women with HIV, lower nadir CD4 + cell counts and hepatitis C virus infection were associated with lower DLCO measurements. Conclusions: HIV was associated with impaired respiratory gas exchange in women. Among women with HIV, lower nadir CD4 + cell counts and hepatitis C infection were associated with decreased respiratory gas exchange. Abstract : In this multicenter cohort of women with and without human immunodeficiency virus (HIV), HIV infection was associated with impaired respiratory gas exchange. Among participants with HIV, lower nadir CD4 + cell counts and hepatitis C infection were also associated with decreased respiratory gas exchange.